Increased osteoclastogenesis contributes to bone loss in the Costello syndrome Hras G12V mouse model - Nandi, Sayantan; Chennappan, Saravanakkumar; Andrasch, Yannik; Fidan, Miray; Engler, Melanie; Ahmad, Mubashir; Tuckermann, Jan P.; Zenker, Martin; Cirstea, Ion Cristian (Frontiers in Cell and Developmental Biology, 2022)
RAS GTPases are ubiquitous GDP/GTP-binding proteins that function as molecular switches in cellular signalling and control numerous signalling pathways and biological processes. Pathogenic mutations in RAS genes severely affect cellular homeostasis, leading to cancer when occurring in somatic cells and developmental disorders when the germline is affected. These disorders are generally termed as RASopathies and among them Costello syndrome (CS) is a distinctive entity that is caused by specific HRAS germline mutations. The majority of these mutations affect residues 12 and 13, the same sites as somatic oncogenic HRAS mutations. The hallmarks of the disease include congenital cardiac anomalies, impaired thriving and growth, neurocognitive impairments, distinctive craniofacial anomalies, and susceptibility to cancer. Adult patients often present signs of premature aging including reduced bone mineral density and osteoporosis. Using a CS mouse model harbouring a Hras G12V germline mutation, we aimed at determining whether this model recapitulates the patients’ bone phenotype and which bone cells are driving the phenotype when mutated. Our data revealed that Hras G12V mutation induces bone loss in mice at certain ages. In addition, we identified that bone loss correlated with an increased number of osteoclasts in vivo and Hras G12V mutations increased osteoclastogenesis in vitro. Last, but not least, mutant osteoclast differentiation was reduced by treatment in vitro with MEK and PI3K inhibitors, respectively. These results indicate that Hras is a novel regulator of bone homeostasis and an increased osteoclastogenesis due to Hras G12V mutation contributes to bone loss in the Costello syndrome.